Recuperação judicial de grupos de sociedades - Fontana, Maria Isabel Vergueiro de Almeida (2017)
Analysis of the corporate groups under a corporate, procedural and concursal point of view and the consequences related to the inadequacy of the Corporate Law (Law 6404/76) in stipulating the total autonomy of the companies that compose the groups and also the omission of Bankruptcy Law (Law 11.101/05) about the judicial reorganization of corporate groups. Study of the procedural and substantial consolidation as exceptional measures to be adopted in judicial reorganization proceedings of corporate groups. Examination of the unfolding of the judicial reorganization jointly requested, such as presentation of the creditors lists and judicial reorganization plan, and how the creditors meetings, voting and quorum shall take place